ChemInform Abstract: Bond‐Forming Reactions of Small Triply Charged Cations with Neutral Molecules. Issue 45 (14th October 2013) - Fletscher, James D.; Parkes, Michael A.; Price, Stephen D.
Abstract Time‐of‐flight mass spectrometry reveals that I3+ reacts with small molecules like SO2, CS2, CH3Cl, CHF3, N2O, CO2, and CO to generate molecular monocations and molecular dications containing iodine such as IO2+, IS2+, IO+, IS+, IC+, ICl2+, ICl+, IF2+, IF+, IN2+, IN+, and IC2+.